2012
DOI: 10.1371/journal.pone.0039013
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities and Mortality in Europe – Results from a Large Multi-National Cohort

Abstract: BackgroundSocio-economic inequalities in mortality are observed at the country level in both North America and Europe. The purpose of this work is to investigate the contribution of specific risk factors to social inequalities in cause-specific mortality using a large multi-country cohort of Europeans.MethodsA total of 3,456,689 person/years follow-up of the European Prospective Investigation into Cancer and Nutrition (EPIC) was analysed. Educational level of subjects coming from 9 European countries was recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 36 publications
7
98
1
5
Order By: Relevance
“…This finding is consistent with most existing studies [16] [17]. People with a lower education level experience a higher burden of cancer [17].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with most existing studies [16] [17]. People with a lower education level experience a higher burden of cancer [17].…”
Section: Discussionsupporting
confidence: 92%
“…Time trend studies have shown that absolute inequalities in cerebrovascular disease mortality are declining in many European countries, and reported larger reductions in death rates among the less educated individuals 20. Gallo and colleagues21 estimated that the least educated European men and women had a 42% and 41% overall excess risk of age-adjusted stroke death, respectively. In our analysis of middle-aged European adults initially free of cardiovascular disease, inequalities between the least and most educated were more commonly observed for stroke incidence than for stroke death rates, being statistically significant in 8 out of the 13 investigated populations in men and in 5 out of 11 in women.…”
Section: Discussionmentioning
confidence: 99%
“…First, in most regions and gender groups, the major contributors to educational inequalities in stroke incidence were behavioural risk factors, that is, cigarette smoking, alcohol intake and BMI. From the paper by Gallo et al ,21 it is possible to infer that the same behavioural risk factors, in addition to the levels of physical activity and vegetable and fruit consumption, explain up to 39.7% and 18.4% of the risk in men and women, respectively. The presence of a synergistic effect of smoking with low education on the risk of stroke8 and cardiovascular diseases23 would suggest that targeting the most disadvantaged individuals might be worthwhile in order to reduce both inequalities and disease rates at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic inequalities in mortality and selfreported morbidity have been extensively documented in national and international studies [1][2][3][4][5][6][7]. For both of these outcomes, and either defined by educational or income level, rates are higher in the lower socioeconomic groups.…”
Section: Introductionmentioning
confidence: 99%